Digestibilidade de dietas e avaliação de alimentos protéicos em sagui-de-tufo-preto (Callithrix penicillata) - Erika Von Zeidler Stasieniuk (2009)
The experiment one was conducted to evaluate and compare the consumption of dry matter energy and protein of five experimental diets for Callithrix penicillata. We used 30 blacktufted-ear-marmoset (Callithrix penicillata) sexed, distributed randomly into five experimental treatments in two different periods, featuring a design in randomized blocks. Four aliments included in the reference ration were tested, on the percentage of 29,25% of the natural matter. The tested aliments were: soybean meal, micronized soybean, and beer yeast and poultry by-products. The results show that there was a large variation in consumption of dry matter per kg of metabolic weight, which ranged from 40,15 to 47,54 g per day. Apparently, there was no control of ingestion by the energy. The palatability may have been the main factor in the regulation of consumption, emphasizing the importance of the voluntary intake and the development of diets for Callitrichideos. The gross consumption of energy per kg of metabolic weight was much higher when compared toother studies found. The experiment two aimed to determine and compare the nutrient digestibility of diets and assess nutritionally complete food protein used for C. penicillata. We used 30 black-tufted-ear-marmoset (C. penicillata) sexed, distributed randomly into five experimental treatments in two different periods, featuring a design in randomized blocks. Four aliments included in the reference ration were tested, on the percentage of 29,25% of the natural matter. The tested aliments were: soybean meal, micronized soybean, and beer yeast and poultry by-products. There were no statistically significantdifferences between the aliments for apparent digestible of energy, digestibility coefficient of dry matter and protein. However, all foods tested showed high digestibility coefficients, can be considered as good options for the composition of diets for C. penicillata.